The handbook of contemporary clinical hypnosis : theory and practice - Brann, Les.; Owens, Jacky; Williamson, Ann, 1950-; Wiley InterScience (Online service) (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
' ... an up-to-date, authoritative resource to support health professionals in their use of hypnosis in clinical settings. Provides an authoritative new reference for practitioners and trainees on the diverse applications of hypnosis, published under the auspices of the British Society for Clinical and Academic Hypnosis (BSCAH) -- Combines a theoretical framework with material on a wide range of specific disorders including anxiety, stress phobias, eczema, oncology, eating disorders and infertility -- Shows how to adjust hypnotic techniques for different contexts e.g. when working with children, in emergencies and via a translator -- Features a variety of case studies that illustrate hypnosis techniques in action.'--Provided by publisher.
The HANDBOOK of CONTEMPORARY ClLINICAL HYPNOSIS: Theory and Practice; Contents; About the Editors; About the Contributors; Foreword; Preface; Part One: Hypnosis: The Fundamentals; 1. Hypnosis: The Theory behind the Therapy; 2. Hypnotic Phenomena and Hypnotizability; 3. History of Hypnosis; 4. Imagery and Visualization; 5. Use of Language and Metaphor; 6. Safety; Part Two: The Stages of Therapy; 7. Initial Steps; 8. Explanation of Hypnosis: The Working Model; 9. Induction and Deepening; 10. Establishing the Problem; 11. Resolving the Problem; 12. Ego Strengthening, Anchoring and Re-alerting.
Includes bibliographical references and indexes.
Print version record.
Keywords: Hypnotism -- Therapeutic use; Hypnosis -- methods; Mental disorders -- Therapy; MEDICAL -- Psychiatry -- General; Hypnotism -- Therapeutic use; Electronic books